PENGARUH BRAND CHARACTERTIC, COMPANY CHARACTERISTIC, DAN CONSUMER BRAND CHARACTERISTIC TERHADAP BRAND LOYALITY PADA KONSUMEN AIR MINUM AQUA DI KOTA KENDAL - Mulazamah, 08.05.51.0056 (Students Journal of Economic and Management, 2013)
The main of this research is to test ofÂ  Brand Charactertic, Company Characteristic, and Consumer Brand Characteristic to Brand Loyality Aqua Consumer in Kendal. The sample that use in this reseach 100 respondent withÂ  questioner method (angket). The data was analyze with analyze factorÂ  to test of validity to question item. alpha Cronbach to test reliabilitas instrument, regresi analysis to fine the influent of independent variable to dependent variable. Base on outcome analysis there was no positive influent and significant effect between brand characteristic (X1) to Brand Loyality (Y), there was positif signifikan influen between company charactristic (X2) to Brand Loyality (Y), there was positif and significant Consumer Characteristic (X3) to Brand Loyality (Y). F test show brand characteristic (X1), company charactristic (X2), Consumer haracteristic (X3) have significant to variabel Brand Loyality (Y). independent variable influent to dependent variable 60.7% the rest is 39.3% influent by other variable that doesnât use in this research. Â  Keyword : Brand Characteristic, Company Charactristic, Consumer Characteristic, Brand Loyality.